Polymer‐Supported Sulfonic Acid‐Catalyzed Candid Synthesis and Photophysical Properties of 2H‐indazolo[2, 1‐b]phthalazinetriones. (4th June 2014) - Mulik, Abhijeet; Chandam, Dattatraya; Patil, Prasad; Patil, Dayanand; Jagdale, Suryabala; Sankpal, Sandip; Deshmukh, Madhukar
<x xml:space="preserve">Abstract</x> Polystyrene‐supported sulfonic acid has been found to be an efficient catalyst for the one‐pot, three‐component synthesis of 2H‐indazolo[2, 1‐b]phthalazinetriones in greener solvent glycerol. Use of greener solvent glycerol along with a polymer‐supported, low toxic, and inexpensive catalyst renders the method eco‐friendly. High yields, simple product isolation procedure, and fluorescent and electroluminescent natures of the products are the noteworthy aspects of this protocol.